Improving Leadership Education Through The GENZED (Gen-Z Get Ready To Lead) Program For New Public Health Science Students - Esrarf, Lubna Salsabila; Mulmaijah, An Nur Ghamiyyu; Pramudya, Dandy Arie; Dhiaulhaq, Dhiaulhaq; Hayuningrat, Fathimah Az-Zahra; Ardiningrum, Hapsari; Annajah, Nabiilah; Mauliddina, Niar Eka; Apriliani, Putri Naya; Desandyansyah, Salmania Khnsa' Nabila; Nazilah, Yasmin (Inovasi Lokal, 2024)
The soft skills needed in this era are leadership skills. The era of society 5.0 will be dominated by generation Z which consists of people born since 1995 who are often called the digital generation or millennial generation. Students have an important role as determining national cadres in advancing and building the country's progress. With the important role of students as agents of change, it is necessary to improve their quality by providing education on how to become leaders in the future by becoming ideal leaders. The Genzed program is here as an educational program about leadership. The aim of the Genzed program is as an effort to increase knowledge among New Students Class of 2023 Offering F Public Health Science Study Program, Faculty of Sports Sciences, State University of Malang. The method used in this research is quantitative methods as the main approach. In the data collection process, this research used an instrument in the form of a pretest-posttest in the form of a multiple choice test with a total of 10 questions. The results obtained from the implementation of the Genzed Program were that overall, the program ran smoothly and received a good response because all participants helped in making the activity a success. Based on the results of completing the pre-test and post-test, there was an increase in the description of the participants' level of knowledge. This, this shows that the Genzed educational program provides sufficient benefits and positive impacts for activity participants.